Financial Technology Adoption and Student Invesment Decisions: The Mediating Role of Investment Interest (Evidence from Students of Universitas Trunojoyo Madura) - Ummah, Afaful; Gazani, Hawa; Ilmi, Moh Miqdad; Zahro, Umi Indasyah; Iman, Aldi Khusmufa Nur (IAIN Kudus, 2025)
The development of financial technology (fintech) has changed the access patterns and investment behavior of the younger generation, including students. However, the level of student investment participation in certain contexts is still relatively low. This research aims to analyze the influence of financial technology on students' investment decisions and examine the mediating role of investment interest in this relationship. This research uses a quantitative approach with a survey method of 30 Trunojoyo Madura University students who have active accounts and have made transactions in the capital market. The limited sample size reflects the relatively small empirical conditions of the target population, so this research is contextual and focuses on the depth of analysis of student investment behavior. Data was analyzed using Partial Least Squares (PLS) via SmartPLS 4.0. The research results show that financial technology has a significant effect on investment interest, but does not have a direct effect on investment decisions. Investment interest is proven to act as a mediator that bridges the influence of financial technology on student investment decisions. These findings provide a theoretical contribution by strengthening the application of the Theory of Planned Behavior in the context of technology-based investment, as well as a practical contribution to the management of the Sharia Investment Gallery in designing strategies to increase student participation that not only focus on technological aspects, but also shape investment interest. The novelty of this research lies in testing the mediating role of investment interest in the context of students with limited levels of investment participation.